2013
DOI: 10.1016/j.intimp.2013.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Vasopeptidase-activated latent ligands of the histamine receptor-1

Abstract: Whether peptidases present in vascular cells can activate prodrugs active on vascular cells has been tested with 2 potential latent ligands of the histamine H 1 receptor (H 1 R). First, a peptide consisting of the antihistamine cetirizine (CTZ) condensed at the N-terminus of ε-aminocaproyl-bradykinin (εACA-BK) was evaluated for an antihistamine activity that could be revealed by degradation of the peptide part of the molecule. CTZ-εACA-BK had a submicromolar affinity for the BK B 2 receptor (B 2 R; IC 50 of 59… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…The umbilical vein contractility assay did not show a loss of apparent potency in the presence of the DPP-IV inhibitor NVP-DPP728 ( Figure 5B ; Table 2 ). Alternatively, BK could be regenerated by two enzymatic cycles catalyzed by aminopeptidases widely expressed in blood vessels, such as aminopeptidase N (Gera et al, 2013b). The aminopeptidase inhibitor amastatin also failed to modify the contractile effect of Arg-Pro-BK ( Figure 5B ; Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The umbilical vein contractility assay did not show a loss of apparent potency in the presence of the DPP-IV inhibitor NVP-DPP728 ( Figure 5B ; Table 2 ). Alternatively, BK could be regenerated by two enzymatic cycles catalyzed by aminopeptidases widely expressed in blood vessels, such as aminopeptidase N (Gera et al, 2013b). The aminopeptidase inhibitor amastatin also failed to modify the contractile effect of Arg-Pro-BK ( Figure 5B ; Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…The latter finding does not automatically apply to all isolated blood vessels, as the BK contractile effect on the rabbit isolated jugular vein was clearly potentiated by enalaprilat treatment (Gera et al, 2011). Previous immunohistochemistry and immunofluorescence studies showed that the umbilical vein possesses a relatively thick media composed of ~30 layers of compactly organized smooth muscle cells (positive for α-actin), while immunoreactive ACE is represented in the single endothelial cell layer (Koumbadinga et al, 2010; Gera et al, 2013b). By comparison, the rabbit jugular vein is very thin, with a higher endothelium/smooth muscle ratio.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Gera et al. ). The assay demonstrates that the vascular pharmacology of DM199 is dependent on kinin release from an exhaustible supply of LMW‐KNG, as shown by the loss of contractility following kininogen depletion and restoration of contractility following exogenous LMW‐KNG addition (Figs.…”
Section: Discussionmentioning
confidence: 98%
“…Histamine mediates its effects through binding to G protein‐associated histamine H 1–4 receptors, resulting in activation of different signal transduction pathways [1,2]. Many of the allergic actions of histamine are mediated via H 1 R, such as redness, itching, and swelling [3,4]. H 1 R has a broad distribution in the central nervous system [5–7].…”
Section: Introductionmentioning
confidence: 99%